COGNITIVE IMPAIRMENT IN PATIENT WITH CHRONIC KIDNEY DISEASE - Yusika Saftari Handini; Ilsa Hunaifi (Faculty of Medicine Universitas Mataram, 2022)
Chronic kidney disease (CKD) is a disease with various causes that result in a progressive decline in kidney function and ends with kidney failure. The cause of kidney damage is an increase of body urea levels which can damage all cells, including neuron cells. Continuous brain cell damage can impair cognitive function. Commonly, cognitive impairment in patient with CKD is caused by 4 factors, include azotemic syndrome, hemodialysis, vascular risk factors and the presence of comorbidities. Azotemic syndrome occurs due to increased levels of urea and creatinine in the blood which can cause Uremic encephalopathy, a complex process associated with decreased cognitive function. Patients undergoing prolonged hemodialysis cause a decrease in cerebral perfusion and a decrease in blood flow velocity, resulting in a decrease of oxygen metabolism in the brain which causes a decrease in cognitive function. Cardiovascular system disorders in patient with CKD show cerebral atrophy and white matter lesions reflecting vascular damage and cerebral ischemic areas which are major contributors to cognitive impairment in patient with CKD. The presence of comorbidities such as low levels of hemoglobin and albumin is a significant risk factor for cognitive impairment.